Activating Inert Metallic Compounds for High‐Rate Lithium–Sulfur Batteries Through In Situ Etching of Extrinsic Metal - Zhao, Meng; Peng, Hong‐Jie; Zhang, Ze‐Wen; Li, Bo‐Quan; Chen, Xiao; Xie, Jin; Chen, Xiang; Wei, Jun‐Yu; Zhang, Qiang; Huang, Jia‐Qi (Angewandte Chemie International Edition, 2019)
Surface reactions constitute the foundation of various energy conversion/storage technologies, such as the lithium–sulfur (Li‐S) batteries. To expedite surface reactions for high‐rate battery applications demands in‐depth understanding of reaction kinetics and rational catalyst design. Now an in situ extrinsic‐metal etching strategy is used to activate an inert monometal nitride of hexagonal Ni3N through iron‐incorporated cubic Ni3FeN. In situ etched Ni3FeN regulates polysulfide‐involving surface reactions at high rates. Electron microscopy was used to unveil the mechanism of in situ catalyst transformation. The Li‐S batteries modified with Ni3FeN exhibited superb rate capability, remarkable cycling stability at a high sulfur loading of 4.8 mg cm−2, and lean‐electrolyte operability. This work opens up the exploration of multimetallic alloys and compounds as kinetic regulators for high‐rate Li‐S batteries and also elucidates catalytic surface reactions and the role of defect chemistry. Inert hexagonal Ni3N can be activated by an extrinsic metal‐incorporating strategy with in situ etching that uses cubic Ni3FeN. Vacancy‐rich Ni3FeN catalysts kinetically regulate polysulfide‐involving reactions at high rates for use in advanced lithium–sulfur batteries.